(3fXe GdeYdheGJ GdeMGSHjI dGJNGP GdbQGQGJ (B:s (3eaGgje hJWHjbGJ (B/s - (3C(B-(3SJjaf, ehSchas; (3L, Sjecf, SjGQc s ((3GdQjGV(B: s (3OGQ GdeQjN ddfTQ(B, s, 1989)
(3jgOa gPG GdcJGH Edi JMdjd OhQ fXe GdeYdheGJ GdGdeMGSHjI aj GOGQI GdefTCJ , hjfUH GdEgJeGe aj gPG GdcJGH Ydi OQGSI GdGSJNOGeGJ GdcheHjhJQ aj GdefTCJ Yi fXe GdeYdheGJ GdeMGSHjI (B.(3ceG Cfg jhaQ ddeMSH GdYUQj aQUI GOQGc hJage bOQGJ hMOhO fVe GdchejQJQ MJi jSJWjY Cf jDOj hXjaI HcaGAI haYGdjI YGdjI HGSJNOGe fXe GdeYdheGJ GdeMGSHjI GdEdcJQhfjI GdeYGUQI (B.s
Keywords: (3eMGSHI (B- (3GJNGP GdbQGQs